SEDEKAH LAWANG AGUNG SEBAGAI EKSPRESI RASA SYUKUR MASYARAKAT DESA PERNEK - Mega Trishuta Pathiassana (Jurnal Budaya Nusantara, 2021)
This research aims to find out the origin and meaning of Sedekah Lawang Agung Ritual tradition was growth and developed among community of Pernek Village, Moyo Hulu Sub-district, Sumbawa Besar Regency. This qualitative study employed purposive sampling method with data collection technique by observation and in-depth interview from the informants. The result of this study showed that there were changes in meaning and objective of the tradition implementation. In the beginning, this tradition was intended for refusing reinforcements on plague afflicted the community. However, the meaning turned into gratitude expression for the community over time. On the other hand, this event is also used as culture and tradition promotion media of Pernek Village community impacted to tourism aspect nowadays. This aspect is expected to rise income of the community by economic activity included in part of the tourism activities.